Peningkatan Penguasaan Teknologi Penunjang Bisnis Pada Wanita Generasi Baby Boomers - Hichmaed Tachta Hinggo; Wan Laura Hardilawati; Alum Kusumah; Sulistyandari Sulistyandari (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
There is a view that women, especially in Indonesia, have the main task, namely as housewives, this view continues to be entrenched and rooted in life in Indonesia, to this day many have such assumptions. This condition supports the low Labor Force Participation Rate (TPAK) for women, which is lower than men. Over time and increasing awareness of the role of women, social changes occur in society. The role of women in the family economy continues to increase, the role of women is seen in their participation in building the nation's economy through MSMEs. However, there are obstacles in the form of gaps in mastering technology, especially for women of the baby boomers generation. To improve the ability of baby boomers to maximize business-supporting digital technology, training and providing information related to digital technology and digital marketing is carried out. This activity was carried out smoothly, the owner who is a generation of baby boomers is expected to succeed in reducing the gap in the use of digital technology through this activity.